INITIATION OF CARBIMAZOLE WHEN BASELINE LIVER TRANSAMINASES ARE 3 TO 5 TIMES OF UPPER LIMIT OF NORMAL: A DIRE CLINICAL JUDGEMENT OR AN EVIDENCE-BASED PRACTICE - Wong, Wei Ton; Jafrudin, Nor Aima binti; Ruslan, Muhammad Ruzaini bin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Antithyroid drugs (ATDs) are the first-line treatment options for hyperthyroidism. ATDs are generally avoided when transaminases are >3-5 times the upper limit of normal. We present a case of carbimazole initiation despite transaminitis of almost 5 times the upper limit of normal (ULN). CASE A 69-year-old female with underlying hypertension presented with a 2-week history of worsening palpitations, poor oral intake, lethargy and vomiting. Upon review, her vital signs were stable except for a heart rate of 160 beats/ min. Physical examination demonstrated warm peripheries and fine tremors. ECG revealed atrial fibrillation. IV Propranolol 1 mg was given, and the rhythm reverted to sinus. Initial blood tests showed overt hyperthyroidism, FT4 >78 pmol/L and suppressed TSH <0.005 uIU/ml. Her baseline transaminases were elevated at ALT 231 U/L (5-49 U/L), AST 162 U/L (4-39 U/L), with normal serum ALP and total bilirubin. Since liver transaminases were raised, ATD was not started, but Lugol’s iodine 10 drops thrice daily and Propranolol 40 mg TDS were given. Hepatobiliary ultrasound showed fatty liver disease, while neck ultrasound showed features of Graves’ disease. Static ALT readings of 203 U/L and 237 U/L were recorded later. Lugol’s iodine was discontinued, and T carbimazole 10 mg BD was started. Close monitoring of transaminases was done. One week later, during clinic review, she was well and her ALT improved to 136 U/L with AST 71 U/L, ALP 63 U/L, and total bilirubin level 12 umol/L. CONCLUSION According to the American Thyroid Association (ATA), patients with transaminases >5 times the ULN should reconsider before initiating ATDs. However, ATDs can be cautiously trialed in such patients with transaminitis, provided liver function is closely monitored. In such circumstances, methimazole is recommended over PTU due to reduced hepatotoxicity risk.